Representação da informação de objetos de aprendizagem por meio de metadados: considerações sobre granularidade e modularidade - Souza, Ráisa Mendes Fernandes de (2020)
The current historical period has been marked by the progressive presence of information and communication technologies in human relations, which is also occurring in educational contexts. That is how learning objects were developed, defined initially and generically, as any digital content directed to education. One of the most prominent characteristics of learning objects is their capacity of reuse in other educational contexts other than the one that originated them. In order to guarantee their complete reuse, it is necessary to carefully analyze solutions that involve an adequate description of their metadata, taking into consideration its granularity and modularity. Starting from the problem configured by the inexistence of a model of representation of the information that considers the granularity and the modularity of the learning objects, in order to make a better recuperation of educational contents possible, this investigation intends to answer the following question: how to represent a learning object through its metadata, considering its granularity and modularity? The general objective of this work is to propose a model of representation through metadata focusing on the granularity and the modularity of the learning objects. The specific objectives are: to build the concept of informational granularity and modularity applied to the context of the learning objects; to investigate the patterns of existent metadata that intend to describe the learning objects, taking into consideration their aspects of form and content; to point out the indispensable elements to the representation of a learning object, considering its characteristics of granularity and modularity; lastly, to structure a model of representation to the learning objects, considering informational granularity and modularity. The research is underpinned by the hypothesis that the proposition of a model of representation of metadata that involves the granularity and the modularity of the learning objects enables a new perspective of organization, access and recuperation of these objects inside a repository of learning objects, potentializing the reuse of these digital resources. The research uses as its empirical universe, the collection of educational resources on health that belongs to the Ministry of Health.Through the application of the Quadripolar Method, constituted by the epistemological, theoretical, technical and morphological poles, it was possible to make the delineation of an operational model of learning object under the perspective of Information Science, gathering three distinct granularity layers: groups os learning objects, learning objects and information assets. Modularity, in the scope of this research, was exposed in a distinct manner, without any categories, thus being analyzed based on it's presence in the content of a digital object. As an additional result, a worflow was presented in order to point out in which stages of the digital objects description the layers of the learning object model proposed were present. It is reckonized the accomplishment of the quadripolar method application in the context of this research, containing all of its poles and showing that the relations between them are not always linear. The learning object operational model, the information representation model and the workflow as well are morphological pole's products. The reflections developed in this thesis points out a lack of scientific works on modularity and granularity in Information Science field.